Pengaruh Kualitas Produk, Harga dan Brand Awareness Terhadap Keputusan Pembelian Produk Merek Scarlett Di Kabupaten Mamuju - Aco, Nur Asia (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2023)
This study aims to determine the effect of Leadership Style and Work Discipline variables on employee performance at the Kalukku Sub-district Office, Mamuju Regency. The research method used is by using quantitative methods with primary data using a questionnaire. Respondents in the study were all employees who worked at the Kalukku Sub-District Office, the sample used was total/saturated sampling technique with a total sample of 33 respondents. The formula in this study uses multiple linear regression, validity test, reliability test, multiple linear regression, t test, and f test. The results in this study indicate that Leadership Style and Work Discipline have a partial and significant effect on employee performance at the Kalukku Sub-district Office, Mamuju Regency. Leadership Style and Work Discipline have a simultaneous and significant effect on employee performance at the Kalukku Sub-district Office, Mamuju Regency.